2022
DOI: 10.4103/iju.iju_166_21
|View full text |Cite
|
Sign up to set email alerts
|

Focal therapy for localized prostate cancer – Current status

Abstract: Focal therapy (FT) has recently gained popularity for the treatment of localized prostate cancer (PCa). FT achieves cancer control by targeting the lesions or the regions of the cancer and avoids damage to the surrounding tissues thus minimizing side effects which are common to the radical treatment, such as urinary continence and sexual function, and bowel-related side effects. Various ablative methods are used to deliver energy to the cancerous tissue. We review the different modalities of treatment and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Currently, a myriad of focal treatment modalities is available for the ablation of prostate cancer. These encompass cryotherapy, high-intensity focused ultrasound (HIFU), irreversible electroporation, photodynamic therapy, and focal brachytherapy [13].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Currently, a myriad of focal treatment modalities is available for the ablation of prostate cancer. These encompass cryotherapy, high-intensity focused ultrasound (HIFU), irreversible electroporation, photodynamic therapy, and focal brachytherapy [13].…”
Section: Discussionmentioning
confidence: 99%
“…Photodynamic therapy (PDT) shares some similarities with FLA, as it also employs transperineally inserted optical fibers directed at the prostate target. However, it is noteworthy that Azzouzi et al reported a notable rate of 38% for erectile dysfunction and urinary complications associated with PDT [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations